Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Perusahaan Daerah Air Minum (PDAM) Sumber Pocong Kabupaten Bangkalan - Prabowo, M. Arif; Faridz, Raden; Burhan, Burhan (Universitas Trunojoyo Madura, 2022)
Clean water is a vital community need that needs special attention. The government needs to provide it adequately as a form of the mandate of the 1945 Constitution. Perusahaan Daerah Air Minum (PDAM), as a representation of the government, becomes an institution that takes on a role in meeting the needs of clean water. The increasing demand for clean water with a rising population needs to be balanced with good service. This research uses a case study in PDAM Sumber Pocong Bangkalan. PDAM Sumber Pocong serves various community needs, including registration, checking water bills, to payment. The assessment of service quality at PDAM Sumber Pocong is expected to be an input to improve the company's performance in the context of service. Customer satisfaction is a measure of service quality performance. This study aims to measure service quality and customer satisfaction of PDAM Sumber Pocong Bangkalan clean water and determine the effect of service quality and customer satisfaction. Three indicators of service quality (reliability, assurance, and facilities) and four customer satisfaction indicators (product quality, price or cost, service, and emotion) proved to be appropriate and relevant measures. Meanwhile, from the path analysis test, the service quality variable has a significant effect on the customer satisfaction variable.